Educating Educational Leaders in a Blended Professional Doctorate Program: An Initial Action Research Inquiry - Kathryn Strom; Bradley Porfilio; Bobbie Plough (Impacting Education, 2016)
This paper describes the first cycle of an action research study investigating the impact of new blended learning courses in a professional doctorate program, the results of which will inform future course planning and pedagogy.  Specifically, core researcher-faculty members associated with the program were interested in understanding how a blended learning program impacted students’ learning experiences. In our findings from this initial inquiry, we detail both constraining and enabling elements of the hybrid experiences provided to students. We also describe the revised action plan created from these findings to improve our ability to utilize the online portion of our doctoral coursework to meet our larger goals of preparing educational leaders to fight for issues of social justice in K-12 settings and beyond.